The Use of Command Strategies by Dave’s Mother in A Novel Entitled "A Child Called ‘It’" - Dini Luthfiani (Lexicon, 2014)
This research attempts to identify the types of commands, forms of command, and three levels of meaning of commands used by Dave’s mother in a novel entitled: A Child Called ‘It’.The data of this research are the commands made by Dave’s mother in the novel entitled:A Child Called ‘It’ written by Dave Pelzer. The findings show that there are two types of command found in the novel which are direct and indirect command. Direct command is the most dominant type used by Dave’s mother. Furthermore, it is found that there are three levels of meaning found in the commands uttered by Dave’s mother; abstract meaning, contextual meaning, and force.